Endothelial activation in experimental metastasis models - Ferjancic, S; Spela Ferjancic (2011)
The majority of cancer related deaths occur due to the invasive growth of metastatic lesions. In the early stages of metastasis, circulating cell interact with the endothelial cells to establish at a distant site. In inflammation endothelial activation results in induction of adhesion molecules on the endothelium that participate in the homing of leukocytes. Because of the interactions of metastatic cells with the endothelium, the question was whether some of the characteristic molecules of endothelial activation were induced during metastasis. In vivo pulmonary metastatic models were used to characterize the expression profile of endothelial activation. Immunohistochemistry identified VCAM-1 to be induced on the pulmonary endothelium following tumour cell arrest. VCAM-1 upregulation was not observed prior to tumour cells arrest or within the first hours. In contrast, tumour cell arrest appeared to be required for endothelial activation, arguing against a mechanism analogous to leukocyte homing. The upregulation of VCAM-1 upon tumour cell arrest corresponded with the initiation of platelet clot formation around the tumour cell and recruitment of leukocytes to the site, both previously shown to be essential for metastasis. Disruption of both phenomena, either through genetic or pharmacological manipulation, demonstrated that in contrast to the recruited leukocytes, platelets were involved in inducing endothelial activation. Another protein investigated was VAP-1. In contrast to VCAM-1, central to VAP-1 adhesive function is its enzymatic activity. Blocking the functions of either molecule highlighted their role in facilitating the recruitment of the leukocyte population to the tumour cell. Disruption of which led to a significant attenuation of metastasis. While VCAM-1 and VAP-1 function appears critical in the early steps of metastasis, their inhibition had no effect at later stages of pulmonary colonization.